Advantages of Nyhus versus Lichtenstein technique for surgical treatment of bilateral inguinal hernia - José Miguel Alfonso Valdés; Luisbel Correa Martínez; Denis Luis Domínguez Rodríguez; Juan Carlos Delgado Fernández; Carlos Alberto Cabrera Rodríguez (Revista de Ciencias Médicas de Pinar del Río, 2019)
Introduction: Lichtenstein's and Nyhus techniques represent safe hernioplasties; Nyhus is a procedure not yet reported as the choice for bilateral inguinal hernia.